Real-Time Stacking System for dangerous containers in seaport terminals. Issue 3 (2015) - Rekik, Ines; Elkosantini, Sabeur; Chabchoub, Habib
Abstract: In container terminals, many operations occur within the storage area including import, export and shifting containers. These operations must respect a set of rules and constraints in order to guarantee an optimal management of the storage area and ensure the port safety during the handling of dangerous goods. However, many unexpected events may occur and affect the storage process and, consequently, scheduled position of containers must be modified. In this paper, we present the architecture of a multiagent based container stacking system to handle different types of containers including containers with dangerous goods. The aim of the developed system is the real time control of seaport terminals and the determination of the exact position of each import container.